Use of traditional medicine versus use of the community-based primary health care clinic by the San community at Platfontein - G. F. de Jager; Engela A.M. Prinsloo; Gina Joubert (South African Family Practice)
Introduction: Working amongst a San community led to the observation that, despite the availability of modern healthcare, high mortality and morbidity associated with disease, such as dehydration, malnutrition and tuberculosis, still prevailed. This study aimed to determine how traditional beliefs and customs influenced the utilisation of Western medicine.